An exploratory study on the user experience of foot reflexology therapy using reflexology artifacts - Okere, H.C. (American Institute of Physics Inc., 2015)
The reputation and significance of foot reflexology therapy has continuously been on the rise. It is currently widely used as a complementary therapy, for stress relief and a potential diagnostic tool. In the society nowadays, there exist a lot of reflexology artifacts that claim to be an alternative substitutes to the traditional foot reflexology practice since the practices promote relaxation and stress relief. However, there has been very little or no attention given towards the verification of such anecdote and the identification of the similarities, differences and opportunities these reflexology artifacts offer. This paper hence aims to address this issue through the exploration of the practices. The study examined the interactive nature of four different sets of common reflexology artifacts from both the patients' and the experts' perspective. Data were collected through audio recorded semi-structured interview. The study findings revealed answers to those anecdotes, highlighting the similarities, difference and opportunities these reflexology artifacts offer. Implications for future research were also discussed. Â© 2015 AIP Publishing LLC.